2020
DOI: 10.18502/fid.v17i30.4751
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transportation of Curved Canals Following Glide Path Preparation by PathFile and Scout RaCe Rotary Systems Versus Manual Instrumentation Using Cone-Beam Computed Tomography

Abstract: Objectives: This study aimed to assess root canal transportation of curved canals following glide path preparation by PathFile and Scout RaCe rotary systems compared with manual instrumentation with stainless steel (SS) hand files using cone-beam computed tomography (CBCT). Materials and Methods: This in-vitro experimental study was conducted on extracted human mandibular first and second molars (n=51) with 25-45° canal curvature in their mesiobuccal root. All teeth underwent CBCT and were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, casting posts increase the risk of root fracture since they require post space preparation, undergo corrosion, exert wedging effect, and also have high modulus of elasticity. (1,2) In the recent years, new types of intracanal posts have beenwere introduced to the market and have gained increasing popularity due to favorable properties such as optimal mechanical properties, uniform stress distribution, requiring less tooth preparation, superior esthetics, and better light transmission to the apical region, which enhances cement polymerization in this area. (3) A clinical study reported 94.3% survival rate for treatment of endodontically-treated teeth with fiber posts without root fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, casting posts increase the risk of root fracture since they require post space preparation, undergo corrosion, exert wedging effect, and also have high modulus of elasticity. (1,2) In the recent years, new types of intracanal posts have beenwere introduced to the market and have gained increasing popularity due to favorable properties such as optimal mechanical properties, uniform stress distribution, requiring less tooth preparation, superior esthetics, and better light transmission to the apical region, which enhances cement polymerization in this area. (3) A clinical study reported 94.3% survival rate for treatment of endodontically-treated teeth with fiber posts without root fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The root canals underwent root canal treatment 1 mm short of the root length (15±1 mm) with RaCe system. (1) After each change of files, the root canals were rinsed with 3 mL of 2.5% sodium hypochlorite. (17) Excess irrigating solution was suctioned out of the root canal, and the canals were dried with paper points.…”
Section: Introductionmentioning
confidence: 99%